The effect of compaction pressure and sintering time on mechanical properties of a waste metal powder - Ahmad Syazwan, Mohammad (2012)
Waste metal powder usually obtains by metal cutting process and this metal powder commonly disposes. This research proposes a technique or method to reuse this metal powder. However, there are many challenges in using this waste metal powder which are the waste metal powder mix with oil and it is needed to obtained small size of metal powder. This challenge can be solve by pyrometallurgy and filtering process. This research use powder metallurgy process in order to reuse this metal powder. Compaction pressure and sintering are an important in powder metallurgy process, which affects the final performance of the part. This study investigates the compaction pressure and sintering on mechanical properties of waste metal powder which get from cutting the metal. The correlation between the density and mechanical properties of the fabricated porous parts are intensively studied. It is found that the compaction pressure and sintering time will affect the mechanical properties of the waste metal powder.